2012
DOI: 10.3892/or.2012.2129
|View full text |Cite
|
Sign up to set email alerts
|

The expression and functional characterization associated with cell apoptosis and proteomic analysis of the novel gene MLAA-34 in U937 cells

Abstract: Abstract. MLAA-34 is a novel acute monocytic leukemia (M5)-associated antigen (MLAA) that plays a role in the apoptosis of U937 cells. However, the expression and molecular mechanism of MLAA-34 in U937 cells remain largely unclear. Here, we utilized three strategies to gain insight into the expression and molecular functions of MLAA-34 and to identify its interacting proteins and pathways involved in the fine-tuning of the MLAA-34 response. Western blot analysis was performed to assess the expression of MLAA-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…This gene is homologous to the known human CAB39L gene and has been confirmed to be a novel splice variant of CAB39L (5,9). The authors of the present study previously reported that MLAA-34 may act as an anti-apoptosis factor in vitro via interacting with Ras, Wnt or calcium and chemokine signaling pathways, and lentivirus-mediated ectopic expression of MLAA-34 in U937 cells markedly suppressed the spontaneous apoptosis of U937 cells (5,12). Additional clinical studies uncovered that high MLAA-34 expression levels usually indicated unfavorable clinical features of patients with AML, and may be used as an early biomarker for detection of relapse (5,9,12).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…This gene is homologous to the known human CAB39L gene and has been confirmed to be a novel splice variant of CAB39L (5,9). The authors of the present study previously reported that MLAA-34 may act as an anti-apoptosis factor in vitro via interacting with Ras, Wnt or calcium and chemokine signaling pathways, and lentivirus-mediated ectopic expression of MLAA-34 in U937 cells markedly suppressed the spontaneous apoptosis of U937 cells (5,12). Additional clinical studies uncovered that high MLAA-34 expression levels usually indicated unfavorable clinical features of patients with AML, and may be used as an early biomarker for detection of relapse (5,9,12).…”
Section: Discussionmentioning
confidence: 54%
“…In conclusion, the evidence that the wild-type MLAA-34 is an anti-apoptotic factor (12,24) and that overexpression of MLAA-34 was observed in patients with AML with poor response to standard chemotherapy indicated that MLAA-34 is a candidate oncogene. Thus, the present study shed light on the diagnosis and treatment of AML, and MLAA-34 may be a novel marker for AML therapy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations